Estudio de factibilidad de un sistema web para la gestión administrativa y educativa en la parroquia Nuestra Señora de la Merced (Catedral) de Babahoyo - Franco Gil, Danes Santiago (2020)
This research work deals with the feasibility study of a web system for administrative and educational management in the parish "Nuestra Señora de la Merced" (Cathedral), located in the city of Babahoyo. Due to the events that occurred due to the Covid-2019 Pandemic, which caused several difficulties in different institutions, companies or any type of business, where the great need for the use of web applications that allows the user to access the information and carry out any type of procedure. This case study aims to prepare a feasibility study that allows to demonstrate the viability of the implementation of a web application, leading to the improvement of its processes, work efficiency and at the same time providing better customer service.